The Role of Parents in Internalizing Islamic Religious Values and Instilling Noble Character (Akhlaq Al-Karimah) in Children In Minority Areas of Lau Gumba Village, Brastagi District, Karo Regency - Panggabean, Hadi Saputra; Tumiran, Tumiran; Nofianti, Rita; Umat, Hardakwah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The inculcation of Islamic religious values, particularly concerning noble character (Akhlaq al-Karimah), in children is essential. This effort requires the involvement of various elements, not solely relying on formal educational institutions. It becomes more effective when families and communities are actively engaged. The family environment, often referred to as the first and foremost setting for a child's education, plays a critical role. In fostering values of goodness and virtue, parents are encouraged to communicate closely with their children. Parents should ideally serve as role models in all aspects of life for their children. Beyond their role as leaders, parents are primary educators within the household. Ideally, parents should guide, educate, train, teach, and exemplify behaviors that shape their children's character and support their learning activities. In the specific context of Lau Gumba Village, where Muslims are a minority, children are particularly vulnerable to the influences of non-Muslim peers. Additionally, the community's socio-economic conditions and the educational background of parents contribute to varied parenting styles. Some families provide significant attention to their children, while others tend to neglect the importance of family education, placing full responsibility on schools. Consequently, many children exhibit weak religious values. In this village, some children neglect their five daily prayers, fail to fast during Ramadan, consume alcoholic beverages (tuak), smoke, and adopt negative behaviors influenced by their environment's traditions